Classroom Development in Times of System Reform - Altrichter, Herbert; Geisler, Birgit (Swiss Journal of Educational Research, 2018)
Since the first half of the 1990s school systems in German speaking countries have seen a growing stream of political debates and initiatives attempting to transform the governance mode of the education system. Within these discourses the call for innovating teaching and learning has become increasingly important. The paper discusses the question how a system-wide educational reform may be pursued which makes a difference for classroom practice and student learning. Firstly, we explain our understanding of the present policies of «new governance» and the significance of «classroom development» within this concept. Secondly, we discuss some data with respect to the effects of «new «overnance» instruments (such as performance standards, standard-related tests and data feedback) on the regulation and development of classroom practice. In chapter 3 we look at successful strategies of classroom development and discuss their potential for system-wide reform.